A Field Study Examination of Budgetary Participation and Locus of Control. - Brownell, Peter (The Accounting Review, 1982)
Abstract ABSTRACT: The results of this field study are generally consistent with those from a previous laboratory experiment which showed that the relationship between budgetary participation and performance is moderated by the personality variable internal-external locus of control. Internals (individuals who feel that they are in control of their own destinies) appear more job-satisfied and perform better under conditions of high participation. By contrast, externals (individuals who attribute the results of their actions to chance, luck, or fate) are more job-satisfied and perform better under conditions of low participation. The complementary findings of the two studies are considered and the implications of the results in the areas of personnel management and control system design are discussed.